The Pummerer-type reaction mediated ring-opening of 2-alkyl substituted 1-[(2-methoxyethoxy)methoxy]-2-(phenylsulfinyl)cyclopropanes - Manat Pohmakotr (2018)
α-Lithiated 1-[(2-methoxyethoxy)methoxy]-2-(phenylsylfinyl)cyclopropane reacted smoothly with alkylating agents to afford the corresponding α-alkylated cyclopropylsulfoxides, which underwent the Pummerer-type reaction mediated ring-opening at low temperature (-78°C) by employing TFAA/Pri2NEt/CH2Cl2to give mixtures of β-(phenylthio)-α,β- and γ,δ-unsaturated aldehydes. © 2001 Elsevier Science Ltd.